2012
DOI: 10.1111/j.1600-6143.2012.04247.x
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Sialoadhesin: A Newly Identified Xenogeneic Innate Immune Receptor

Abstract: Extracorporeal porcine liver perfusion is being developed as a bridge to liver allotransplantation for patients with fulminant hepatic failure. This strategy is limited by porcine Kupffer cell destruction of human erythrocytes, mediated by lectin binding of a sialic acid motif in the absence of antibody and complement. Sialoadhesin, a macrophage restricted lectin that binds sialic acid, was originally described as a sheep erythrocyte binding receptor. Given similarities between sialoadhesin and the unidentifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 75 publications
0
30
0
Order By: Relevance
“…In addition to releasing pro-inflammatory and pro-coagulant factors, pig alveolar lung and spleen macrophages and liver Kuppfer cells bind to and phagocytose human blood cells through innate cellular carbohydrate recognition by the porcine lectin sialoadhesin (23). …”
Section: Text Of Reviewmentioning
confidence: 99%
“…In addition to releasing pro-inflammatory and pro-coagulant factors, pig alveolar lung and spleen macrophages and liver Kuppfer cells bind to and phagocytose human blood cells through innate cellular carbohydrate recognition by the porcine lectin sialoadhesin (23). …”
Section: Text Of Reviewmentioning
confidence: 99%
“…However, pretreatment of donors would be acceptable for xenotransplantation. In xenotransplantation, porcine KCs directly recognize a sialic acid motif on human glycophorin A and destroy human erythrocytes . We speculate that the strategy of KC replacement might be useful in making clinical xenotransplant trials feasible.…”
Section: Discussionmentioning
confidence: 99%
“…While literature on carbohydrate-mediated skewing of Th17 differentiation is predominantly from models of infection(46, 47), it has recently been shown that such a skewing may also play a role in transplantation rejection such as graft-versus-host disease (GVHD)(48). Recognition of xenogeneic carbohydrates by lectin receptors has been described in discordant xenogeneic transplantation models to promote phagocytosis of xenogeneic (human) erythrocytes and platelets by porcine macrophages(49, 50). Interestingly, lectin receptor on CD4 T cells has also been associated with a propensity of their differentiation towards Th17 cells(51) and an increased risk for GVHD(52).…”
Section: Discussionmentioning
confidence: 99%